Bone-Forming Capabilities of a Newly Developed NanoHA Composite Alloplast Infused with Collagen: A Pilot Study in the Sheep Mandible - Charles Marin; Ryo Jimbo; Fabio Cesar Lorenzoni; Lukasz Witek; Hellen Teixeira; Estevam Bonfante; Jose Gil; Rodrigo Granato; Nick Tovar; Paulo G. Coelho (International Journal of Dentistry)
Lateral or vertical bone augmentation has always been a challenge, since the site is exposed to constant pressure from the soft tissue, and blood supply only exists from the donor site. Although, for such clinical cases, onlay grafting with autogenous bone is commonly selected, the invasiveness of the secondary surgical site and the relatively fast resorption rate have been reported as a drawback, which motivated the investigation of alternative approaches. This study evaluated the bone-forming capability of a novel nanoHA alloplast infused with collagen graft material made from biodegradable polylactic acid/polyglycolic acid versus a control graft material with the same synthesized alloplast without the nanoHA component and collagen infiltration. The status of newly formed bone and the resorption of the graft material were evaluated at 6 weeks in vivo histologically and three dimensionally by means of 3D microcomputed tomography. The histologic observation showed that newly formed bone ingrowth and internal resorption of the block were observed for the experimental blocks, whereas for the control blocks less bone ingrowth occurred along with lower resorption rate of the block material. The three-dimensional observation indicated that the experimental block maintained the external geometry, but at the same time successfully altered the graft material into bone. It is suggested that the combination of numerous factors contributed to the bone ingrowth and the novel development could be an alternative bone grafting choice.